Implementasi Animasi Tarian Daerah Dengan Menggunakan iClone (Studi Kasus : Tari Gambyong) - Marsela, Yonenda; , Drs. Sujalwo, M. Kom (2016)
Video is one of the media is easy to influence people, both adults and children. With the rapid development of information and communication technology today, many media are used as a medium of learning for children, and to facilitate the absorption of information and knowledge in learning. One is an animated video that is suitable for the media. Video animation that originally could only be as a media entertainer has now also become a tool to provide learning through meaning, purpose, and entries presented here. The art of dance is a legacy that reflects local wisdom. Gambyong Dance of Solo is one that must be maintained. The existence of the dance in the style of animated videos can deliver maximum entertainment and education.